Meningkatkan Pengetahuan Konsumsi Serat Dikalangan Mahasiswa Menggunakan Media Audio dan Visual - Elzalika Aisyiyah Agsya; Nur Hikmatul Alia; Yusmiati Yusuf; Ajiza Ariani; Imanuel Saulanda; Devi Savitri Effendy (Pusat Riset dan Inovasi Nasional, 2025)
Low fiber consumption among university students increases the risk of chronic diseases such as coronary heart disease, and diabetes. Many students prioritize convenient eating habits and are influenced by peer groups, often overlooking the importance of fiber intake in their daily diet. This educational program aims to enhance students' knowledge about the benefits of fiber consumption through interactive audio and visual media. The program applies the Health Belief Model (HBM) theory to design educational content in the form of videos and posters distributed via the social media platform Instagram. Involving 26 student respondents from various faculties at Halu Oleo University, the results showed a significant improvement in students' understanding of the health benefits of fiber, types of fiber-rich foods, and the role of fiber in preventing chronic diseases. Education through engaging media successfully increased students' motivation to improve their dietary habits by incorporating more fiber into their diets.